THE INFLUENCE OF KNOWLEDGE ON ATTITUDES IN EMERGENCY RESPONSE TO FOREST AND LAND FIRE DISASTERS AMONG STUDENTS AT STATE ELEMENTARY SCHOOL 04 RASAU JAYA - Saroh, Nur Mai; Ulfah, Maria; Adlika, Nur Meily (Universitas Tanjungpura, 2024)
SDN 04 Rasau Jaya is a school located in Rasau Jaya Tiga Village, Rasau Jaya Tiga Village is a village included in Karhutla-prone villages and one of the villages that experienced the second largest forest and land fires after Rasau Jaya Dua Village. This study aims to determine the effect of knowledge on the attitude of emergency response to forest and land fires in students of Sdn 04 Rasau Jaya Kubu Raya Regency. This study uses descriptive quantitative research which aims to describe systematically the facts by trying to describe the phenomenon in detail so that researchers can explain how knowledge affects the attitude of emergency response to forest and land fires in students of SDN 04 Rasau Jaya in a structured manner and a sample of 71 people was used. Data were obtained using test instruments and questionnaires and then analyzed using simple linear regression analysis techniques. The results obtained based on the significance value of the Coefficients table obtained a significance value of 0.481 0.05, so it can be concluded that the Knowledge variable (X) affects the Emergency Response Attitude variable (Y).